2014
DOI: 10.1177/0014402914527241
|View full text |Cite
|
Sign up to set email alerts
|

Using Antecedent Physical Activity to Increase On-Task Behavior in Young Children

Abstract: A withdrawal design was used to investigate how physical activity affects on-task behavior of young children with significant developmental delays in a special education preschool classroom. Five preschool age children with significant developmental delays engaged in either physical activity or seated center activities for 20 min prior to a 15-min teacher-directed group activity. Momentary time sampling was used to calculate the percentage of intervals the participants were on-task using 15-s intervals. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…2006; Luke et al . 2014), moderate to vigorous physical activity is performed at lower rates (Whitt‐Glover et al . 2006; Oates et al .…”
Section: Discussionmentioning
confidence: 99%
“…2006; Luke et al . 2014), moderate to vigorous physical activity is performed at lower rates (Whitt‐Glover et al . 2006; Oates et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using pedal desks as physical activity breaks may be more beneficial for impacting on-task behavior than having the pedal desks be an option to use while simultaneously completing the classroom curriculum. Most research on physical activity in the classroom has focused on the use of PA as an isolated activity (Glapa et al, 2018;Luke, Vail, & Ayres, 2014;Mahar, 2011) or has integrated it into the curriculum itself (Fedewa, Fettrow, Erwin, & Ahn, in press;Donnelly & Lambourne, 2011;Goh, Hannon, Webster, Podlog, & Newton, 2016;Kibbe et al, 2011), not provided it as a secondary option while completing academic tasks. In either case, the classroom curriculum is a factor to consider when using pedal desks in the classroom, as the required task could be coded and accounted for as another variable in the relationship between activity and on-task behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Results of this study showed that engagement in physical activity prior to a teacher-led group activity resulted in higher on-task behavior than engaging in seatwork prior to the activity. These results suggest that physical activity can be a useful proactive measure to increase the likelihood of on-task behavior of children with developmental delays in a classroom setting (Luke et al, 2014).…”
Section: Interventions For Classroom Skillsmentioning
confidence: 82%
“…Researchers at the University of Georgia were also interested in how to increase the on-task behavior of children with disabilities in the classroom setting. They examined how physical activity affected the on-task behavior of five children with significant developmental delays in a special education preschool classroom (Luke, Vail, & Ayres, 2014). The researchers noted that the concept of on-task behavior is defined in the literature in different ways, such as attention to task, academic engagement, and learning related social skills, but for the purpose of this study, on-task behavior was defined as: (a) looking at teacher, (b) keeping hands to self, and (c) singing or imitating movements to songs or poems (Luke et al, 2014).…”
Section: Interventions For Classroom Skillsmentioning
confidence: 99%
See 1 more Smart Citation